In the lap of luxury: Consumer conversation concerning online advertisements of luxury brands - M. Reyneke (South African Journal of Business Management, 2011)
While branding is an area that is extensively studied in the marketing literature, there is a noticeable lack of attention to the study of luxury brands, and even more so from an online perspective. In this exploratory study, we make use of the content analysis software Leximancer to comprehend the consumer feedback around conversations about luxury brand ads posted online.We study consumer comments posted on YouTube around three different luxury brands and analyse these comment in order to find meaning among the large volume of consumer discussion. We attempt to shed some light on how these conversations can be tracked and interpreted in order to gain valuable insight into the consume's role in advertising through discussing the ads for well known luxury brands that were chosen for this study and the subsequent reactions to them. We go on to discuss the Leximancer tool that can be used for deciphering and interpreting the consumer conversations surrounding these ads and the results of the analysis. We conclude by acknowledging the limitations of this methodology, identifying implications for managers, and suggesting avenues for future research.
Keywords: 650